A Dynamic Model of Tourism and Economic Growth: the Role of Physical and Human Capital - Brida, Juan Gabriel (2013)
This paper study the relationships between tourism and economic growth by introducing a dynamic model whose ingredients are an economy producing a non-traded consumption good consumed by domestic residents and foreign tourists and a capital good. The model analyses the relationships between tourism growth, physical and human capital accumulation and changes in the terms of trade. From this analysis, several interesting results are obtained that depend on initial conditions of the main variables and on variations in terms of trade.. First, it is shown that tourism allows local population to enjoy a given welfare level with a lower saving rate than they would have in a closed economic system. Second, it is revealed that along the balanced growth path, the rate of human capital accumulation in the tourism industry acts negatively on the rate of change in the terms of trade. A more productive industry becomes more cheaper and cheaper for the rest of the world and for the residents themselves. Third, it is shown that when prices steadily increase, the model implies an unbalanced relationship between domestic and tourism demands. In that case, the economy could assign all production to internal consumption, vanishing the tourism industry.: or, by the contrary, it could specialize completely in tourism, exporting all production of domestic consumption goods and importing all consumption goods for domestic demand.